Optimal Allocation of Capacitors in Radial Distribution Networks Using Shannon's Entropy - Gupta, Shubham; Yadav, Vinod Kumar; Singh, Madhusudan (IEEE transactions on power delivery, 2022)
Capacitor banks, when optimally placed in an electrical network improve power quality and reliability. For determining the capacitors' optimal location, the prevailing index methods mainly focus on single criterion, e.g., either of voltage stability, loss reduction, system loadability, and neglect some of the equally critical quantities while proving the solution. For obtaining a pragmatically feasible techno-commercial solution, it is advantageous to consider multiple criteria. This article proposes a novel approach for optimal capacitor allocation, which allows to choose as many objective functions (criteria) as desired. In the proposed approach, initially, the load flow study is executed to obtain the network's quantities for an uncompensated network. Subsequently, optimal locations of capacitor banks are identified through the proposed indexing method based on the application of Shannon's Entropy. The capacitor banks' optimal sizes are determined using the particle swarm optimization algorithm. The cost function is formulated as the minimization of sum of active power loss cost and the incurred annual capacitors cost subject to different operational constraints. The proposed approach is compared with that of the previously published methods by applying on radial distribution networks of different sizes (IEEE-12 bus, 34-bus and 108-bus) and the proposed approach is found to be superior.